PROBLEMS FACED BY STUDENTS IN SPEAKING ENGLISH - Wardhani, Wira Mukti; Rafiqa, Syarifa; Makmur, Selamet (Universitas Borneo Tarakan, 2023)
English is an international or global language that individuals from different regions or countries use to help them understand and interact with one another. Indonesian is the national language of Indonesia. One of the language skills that students need to be proficient is speaking, as speaking is the most crucial aspect of the objectives for learning Indonesian. The first goal of this study is to determine students' difficulties in speaking English, and the second is to look for possible remedies. In this research, a case study methodology was carried out. Students of class XII at one of public senior high schools in Tarakan served as the research subjects. Of the 36 students, only 28 per cent (10) were deemed to speak. This study revealed that students' challenges when speaking English are primarily related to a deficiency of vocabulary, challenging grammar, and challenging pronunciation.